Salmeterol in nocturnal asthma: a double blind, placebo controlled trial of a long acting inhaled beta 2 agonist. Issue 6765 (15th December 1990) - Fitzpatrick, M F; Mackay, T; Driver, H; Douglas, N J
Abstract : OBJECTIVE--To determine whether inhaled salmeterol, a new long acting inhaled beta adrenergic agonist, reduces nocturnal bronchoconstriction and improves sleep quality in patients with nocturnal asthma. DESIGN--Randomised, double blind, placebo controlled crossover study. SETTING--Hospital outpatient clinics in Edinburgh. SUBJECTS--Twenty clinically stable patients (13 women, seven men) with nocturnal asthma, median age 39 (range 18-60) years. INTERVENTIONS--Salmeterol 50 micrograms and 100 micrograms and placebo taken each morning and evening by metered dose inhaler. Rescue salbutamol inhalers were provided throughout the run in and study periods. MAIN OUTCOME MEASURES--Improvement in nocturnal asthma as measured by peak expiratory flow rates and change in sleep quality as measured by electroencephalography. RESULTS--Salmeterol improved the lowest overnight peak flow rate at both 50 micrograms (difference in median values (95% confidence interval for difference in medians) 69 (18 to 88) l/min) and 100 micrograms (72 (23 to 61) l/min) doses twice daily. While taking salmeterol 50 micrograms twice daily patients had an objective improvement in sleep quality, spending less time awake or in light sleep (-9 (-4 to -44) min) and more time in stage 4 sleep (26 (6-34) min). CONCLUSIONS--Salmeterol is an effective long acting inhaled bronchodilator for patients with nocturnal asthma and at a dose of 50 micrograms twice daily improves objective sleep quality.